TANTANGAN DALAM PENEGAKAN HUKUM ADMINISTRASI NEGARA DI ERA DIGITAL: PERSPEKTIF PERLINDUNGAN DATA PRIBADI - Amalia, Disa; Aldri Frinaldi (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2023)
The rapid development of information and communication technology has fundamentally changed the legal landscape of state administration. In this digital era, personal data is a very valuable asset and an increasingly important object of protection. However, the challenges in enforcing state administrative law in the digital era, particularly in terms of personal data protection, are increasingly complex and require a comprehensive approach. This article aims to analyze the main challenges in enforcing state administrative law in the digital era with a focus on personal data protection. First of all, the main challenge is the rapid development of technologies, such as the Internet of Things (IoT) and artificial intelligence (Artificial Intelligence), which generate huge and diverse volumes of data. This requires effective protection of personal data and adherence to data protection principles established by law. Another challenge is the increasing frequency of data breaches. In the digital era, personal data is vulnerable to abuse and hacking which can threaten individual privacy and security. Therefore, state administrative law enforcement must be able to overcome this threat by strengthening data protection mechanisms, implementing strict information security policies, and increasing international cooperation in law enforcement related to data breaches. Furthermore, another challenge is the harmonization between state administrative law and personal data protection in the digital era. Existing state administrative laws need to be updated and adapted to technological developments and personal data protection. There is a need for a clear and comprehensive legal framework that protects personal data in line with the principles of a transparent, accountable and effective state administration. In order to overcome this challenge, the government, law enforcement agencies and the private sector need to work together actively to develop comprehensive regulations, increase law enforcement capacity in terms of personal data protection, and increase legal awareness among the public. Only with a holistic approach.